THE EFFECT OF SERVICE QUALITY AND BRAND IMAGE TO IMPROVE THE SATISFACTION AND LOYALTY OF BIGTV CUSTOMERS IN SEMARANG - Pragunadi, Nindita Gabriele; Sukresna, I Made; Sutopo, Sutopo (Master of Management Diponegoro University, 2018)
The problem that happened in this research is the decrease of BIGTV customer loyalty of Semarang which result in customer decision to unsubscribe. This is evident from the increasing number of subscribers who have been subscribed for more than 1 year but unsubscribed in the first half of 2015. So the formulation of this research problem is how to increase customer loyalty BIGTV Semarang and BIGTV Semarang customer decisions to re-subscribe allegedly influenced by the quality service, and brand image. This study aims to analyze the influence of service quality and brand image directly or indirectly to customer loyalty with mediated by satisfaction. Sample selection using purposive sampling. The sample used is 150 people BIGTV Semarang customers. The analysis tool used is structural equation modeling. Based on the results of research, service quality and brand image have a positive effect on satisfaction and loyalty, while satisfaction has a positive effect on loyalty. Based on the fit model test, 7 indicator test result stated that all models have a good fit. So from this, it can be concluded that the model has a good enough fit to predict customer loyalty